2020
DOI: 10.1515/znc-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Selected essential oils and their mechanisms for therapeutic use against public health disorders. An overview

Abstract: AbstractToday, the numbers of people suffering from lifestyle diseases like diabetes, obesity, allergies and depression increases mainly in industrialised states. That does not only lower patients’ quality of life but also severely stresses the health care systems of these countries. Essential oils (EO) have been in use as therapeutic remedies for centuries against various complaints, but still their effectiveness is being underestimated. In the last decades, a great number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 121 publications
0
15
0
Order By: Relevance
“…Chitosan nanostructures (CNSs) are a pressing subject in research fields on the strength of their antioxidant activity. A combination of chitosan and citrus EOs nanostructures leads to a synergetic effect and increase in the antioxidant potential adding important value in food preservation [ 10 ] and food packaging [ 11 ].…”
Section: Polymer-based Nanostructures For Citrus Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan nanostructures (CNSs) are a pressing subject in research fields on the strength of their antioxidant activity. A combination of chitosan and citrus EOs nanostructures leads to a synergetic effect and increase in the antioxidant potential adding important value in food preservation [ 10 ] and food packaging [ 11 ].…”
Section: Polymer-based Nanostructures For Citrus Essential Oilsmentioning
confidence: 99%
“…In addition to the hypolipidemic properties, tangerine EO also presents anti-inflammatory properties and it is widely used for its antidepressant effects [ 9 ]. Orange EO is recognized for a broad list of health-promoting benefits such as anti-obesity effect through reduction of total cholesterol by 17% [ 10 ], antidepressant and anxiolytic [ 11 ], apoptotic and anti-angiogenesis effects on colon cancer cells [ 12 ], anti-inflammatory, neuroprotective, analgesic effects field [ 13 ], etc. Bergamot EO is well recognized in the literature for its anticancer properties and its suitability in food preservation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that essential oils (EOs), thanks to their constituents, promote the reduction of fat mass and exert anti-obesity effects. It is important to note that EOs can exert these effects both when taken with the diet or inhaled [ 7 , 8 , 87 ].…”
Section: Anti-obesity Effect Of Eosmentioning
confidence: 99%
“…Recent studies, performed both with in vivo and in vitro systems, show that essential oils (EOs) exert a broad-spectrum therapeutic potential against obesity and its related-diseases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of CSP EO [13][14][15] is reported in Table 1.Asitcanbe seen, the major component is D-Limonene, accompanied by several minor components belonging to the classes of monoterpene alkenes, oxygenated monoterpenes including alcohol aldehydes and esters, sesquiterpenes as well as linear alkanes and aldehydes. This rather complex blend accounts for the numerous deal of biological activities reported for the CSP EO [14][15][16], which include anthelmintic, antiaflatoxigenic [17], antibacterial [18][19][20], anticarcinogenic, antifungal [21], antioxidant [17], anti-tumor [22], anxiolytic [23], food preservative [24], hepatocarcinogenesis suppressant, insecticidal and larvicidal [25], pain relief and relaxant [26]. It can be argued that the main effects are due to the presence of the major component Limonene that showed several bioactivities when tested as pure compound [27].…”
Section: Essential Oilsmentioning
confidence: 99%